Cytogenetic, crossing and molecular evidence of two cytological forms of Anopheles argyropus and three cytological forms of Anopheles pursati (Diptera: Culicidae) in Thailand - S. Thongsahuan (2018)
Nine and 11 isolines of Anopheles argyropus and Anopheles pursati, respectively, were established from individual females collected from cow-baited traps, and the characteristics of metaphase chromosomes were investigated in their F1-progenies. As determined by the different amounts of extra heterochromatin on sex chromosomes, 2 types of X (X1, X2) and Y (Y1,Y2), and 2 types of X (X1, X2) and 3 types of Y (Y1, Y2, Y3) chromosomes were obtained from An. argyropus and An. pursati, respectively. These types of sex chromosomes comprised 2 [Forms A (X1, Y1) and B (X1, X2, Y2)] and 3 [Forms A (X1, X2, Y1), B (X1, X2, Y2) and C (X2, Y3)] karyotypic forms of An. argyropus and An. pursati, respectively. All karyotypic forms acquired from An. pursati are new one that were discovered in this study, of which Forms A, B and C were found generally in Chiang Mai Province, while only 1 isoline of Form B was obtained in Ratchaburi Province. Form A was recovered from An. argyropus only in Ubon Ratchathani Province, whereas Form B from that species was found commonly in both Ubon Rathchathani and Nakhon Si Thammarat Provinces. Crossing experiments among the 2 and 3 isolines representing 2 and 3 karyotypic forms of An. argyropus and An. pursati, respectively, indicated genetic compatibility in yielding viable progenies and synaptic salivary gland polytene chromosomes through F2-generations. The conspecific natures of these karyotypic forms in both species were further supported by very low intraspecific sequence variations (average genetic distance: An. argyropus = 0.003-0.007, An. pursati = 0-0.005) of ribosomal DNA (ITS2) and mitochondrial DNA (COI and COII).